Beam Dynamics Simulation of Photocathode RF Electron Gun at the PBP-CMU Linac Laboratory - K. Buakor (2018)
© Published under licence by IOP Publishing Ltd. Photocathode radio-frequency (RF) electron guns are widely used at many particle accelerator laboratories due to high quality of produced electron beams. By using a short-pulse laser to induce the photoemission process, the electrons are emitted with low energy spread. Moreover, the photocathode RF guns are not suffered from the electron back bombardment effect, which can cause the limited electron current and accelerated energy. In this research, we aim to develop the photocathode RF gun for the linac-based THz radiation source. Its design is based on the existing gun at the PBP-CMU Linac Laboratory. The gun consists of a one and a half cell S-band standing-wave RF cavities with a maximum electric field of about 60 MV/m at the centre of the full cell. We study the beam dynamics of electrons traveling through the electromagnetic field inside the RF gun by using the particle tracking program ASTRA. The laser properties i.e. transverse size and injecting phase are optimized to obtain low transverse emittance. In addition, the solenoid magnet is applied for beam focusing and emittance compensation. The proper solenoid magnetic field is then investigated to find the optimum value for proper emittance conservation condition.